Cancer Nano-Immunotherapy: The Novel and Promising Weapon to Fight Cancer - García-Domínguez, Daniel J.; López-Enríquez, Soledad; Alba, Gonzalo; Garnacho, Carmen; Jiménez-Cortegana, Carlos; Flores-Campos, Rocío; de la Cruz-Merino, Luis; Hajji, Nabil; Sánchez-Margalet, Víctor; Hontecillas-Prieto, Lourdes (International journal of molecular sciences, 2024)
Cancer is a complex disease that, despite advances in treatment and the greater understanding of the tumor biology until today, continues to be a prevalent and lethal disease. Chemotherapy, radiotherapy, and surgery are the conventional treatments, which have increased the survival for cancer patients. However, the complexity of this disease together with the persistent problems due to tumor progression and recurrence, drug resistance, or side effects of therapy make it necessary to explore new strategies that address the challenges to obtain a positive response. One important point is that tumor cells can interact with the microenvironment, promoting proliferation, dissemination, and immune evasion. Therefore, immunotherapy has emerged as a novel therapy based on the modulation of the immune system for combating cancer, as reflected in the promising results both in preclinical studies and clinical trials obtained. In order to enhance the immune response, the combination of immunotherapy with nanoparticles has been conducted, improving the access of immune cells to the tumor, antigen presentation, as well as the induction of persistent immune responses. Therefore, nanomedicine holds an enormous potential to enhance the efficacy of cancer immunotherapy. Here, we review the most recent advances in specific molecular and cellular immunotherapy and in nano-immunotherapy against cancer in the light of the latest published preclinical studies and clinical trials.